Preferred modalities for delivering continuing education to the public health workforce: a scoping review - Archer, Anya; Berry, Isha; Bajwa, Uttam; Kalda, Robyn; Di Ruggiero, Erica (Health promotion and chronic disease prevention in Canada, 2020)
Continuing education (CE) can help public health professionals maintain and further develop their knowledge and skills to adapt to the changing public health landscape. This scoping review aims to identify the preferred modalities for delivering CE to public health professionals and to determine how equity has been incorporated into public health training. Using the PRISMA extension for Scoping Reviews as a guide, we searched four databases for peer-reviewed primary research studies that evaluated public health workforce CE modalities. The review included 33 studies published between 1 January 2000 and 6 August 2019 from over 11 countries. Most articles broadly described their training audience as public health professionals employed by government or non-governmental organizations. Delivery methods included online, in-person or blended learning (combining online and in-person instruction). Learners strongly preferred self-directed approaches. Organizational support, including protected time for professional development during work hours, was an important enabler of training completion. Commonly cited barriers included course duration and a high number of contact hours. Findings suggest that there is no single preferred training modality. We identified three elements that influence modality preference: design, delivery and organizational support. Modality should be determined by participants' location, needs and previous experiences to ensure the content is relevant and delivered in a way that equips learners to apply the knowledge gained.